MANAGEMENT OF VILLAGE REVENUE AND EXPENDITURE BUDGET IN MARISA DISTRICT - Sri Wahyuni; Hartati Tuli; Lukman Pakaya (PT. Jurnal Center Indonesia Publisher, 2025)
The purpose of this research is to analyze the management of the Village Revenue and Expenditure Budget (APBDes) in Marisa District. This study limits its focus to the aspects of planning, allocation, implementation, supervision and accountability, and reporting of APBDes. This research employs a quantitative method with a descriptive approach. The research population comprises all village officials in Marisa District, totaling 110 individuals, and the sample was drawn using a saturated sampling (census) technique. Data was collected through questionnaires completed by the Village Government. The research findings indicate that the overall management of APBDes in Marisa District is generally very good. APBDes planning is assessed as very good, characterized by transparency in village deliberations, effectiveness in addressing community problems and needs, and alignment of the Village Medium-Term Development Plan (RPJMDes) with community aspirations. Sources